Infant Multiple Mandibular Fracture: Case Report (International Journal of Medical and Surgical Sciences, 2016)
Infant facial fracture incidence is low. Most reported cases affect the jaw and are single fractures. We present a twenty-two-month old patient, who had a high-energy car accident. Among other injures, she suffered a multiple mandibular fracture: bicondylar, left body and right parasymphyseal. Stable internal fixation of parasymphyseal and body mandibular fracture was performed on the third day. Condylar fractures had a functional treatment with switching elastic traction to prevent ankylosis. Computed tomography (CT) showed mandibular condyles remodelling after six months. Clinical examination showed that mandibular movement ranges were preserved without alteration. Successful treatment of paediatric patients is based on the achievement of an adequate anatomic reduction and the stability of the fracture, allowing opportune form and function recovery, in order to assure further development of dental and facial structures.